Dynamic modification of shaping time in x-ray detectors - DUGAS MICHAEL E; GRODZINS LEE (2011)
Methods and apparatus for adapting the shaping time and/or other pulse processing parameters of an x-ray detector (114) in accordance with the elemental composition of a sample and/or energy resolving requirements. X-rays (104) are directed from a source (102) onto a sample (110) and the radiation (108) responsively emitted from the sample (e.g., fluoresced radiation characteristic of the sample's elemental composition) and detected by an x-ray detector (114) that generates pulses representative of the energy and intensity of the incident radiation. Based upon initial analysis of elemental composition, the shaping time and/or other pulse processing parameter (s) are set to optimize count rate subject to constraints of energy resolution in a spectral region of interest.